2004
DOI: 10.1007/s00595-003-2671-7
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Unilateral Adrenal Hematoma: Report of a Case

Abstract: We report an unusual case of idiopathic unilateral adrenal hematoma, which was asymptomatic and unaccompanied by a hematologic disorder. The surgical specimen contained a large tumor comprised of subacute to chronic organized hematoma. The preoperative magnetic resonance imaging findings were compatible with characteristics reported previously, except for spotty strong enhancement in the peripheral part of the mass. It is important to differentiate this benign lesion from a neoplasm, although we were not able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Ovarian tumors, endometrial implants, or ectopic tissues may cause spontaneous retroperitoneal hemorrhage. Kobayashi et al [12] reported a case of unilateral adrenal hematoma, whose radiological findings were similar to our case. Spontaneous or idiopathic adrenal hematoma is also extremely rare, since most adrenal hematoma cases occur in association with trauma or similar causes of idiopathic retroperitoneal hematoma.…”
Section: Discussionsupporting
confidence: 88%
“…Ovarian tumors, endometrial implants, or ectopic tissues may cause spontaneous retroperitoneal hemorrhage. Kobayashi et al [12] reported a case of unilateral adrenal hematoma, whose radiological findings were similar to our case. Spontaneous or idiopathic adrenal hematoma is also extremely rare, since most adrenal hematoma cases occur in association with trauma or similar causes of idiopathic retroperitoneal hematoma.…”
Section: Discussionsupporting
confidence: 88%
“…3 Most adrenal gland haematomas, which are more common in children than adults, are associated with anticoagulant therapy, septicaemia, low blood pressure, tumours, pregnancy complications, or traumas. 1 post-surgical haematoma; adrenal haematomas associated with heparin associated thrombocytopenia; severe stress or sepsis associated haematomas; haematomas due to traumas.…”
Section: Discussionmentioning
confidence: 99%
“…1 Its clinical presentation is typically characterised by acute abdominal pain, fever, low blood pressure, and progressive anaemia, 2 whereas non-symptomatic adrenal gland haematomas are extremely unusual and the lesion is often a large and palpable mass.…”
mentioning
confidence: 99%
“…These lesions were most commonly described as a consequence of trauma, but also in patients taking non-steroidal anti-inflammatory drugs (NSAIDs), with neurofibromatosis, after liver transplantation, with primary and metastatic adrenal tumors, with heparin-associated thrombocytopenia, on anticoagulation, on hormonal therapy, with severe sepsis and anti-phospholipid antibodies [2][3][4]. Spontaneous idiopathic adrenal hematomas were also reported [2,5,7,8]. Clinical presentation of adrenal hematomas varies, and may include flank or abdominal pain (like in our patient), fever, tachycardia, weakness, hypotension, nausea, vomiting, changes in mental status, weight loss, abdominal distention and palpable abdominal mass [2].…”
Section: Discussionmentioning
confidence: 99%
“…They were reported in patients with trauma, long-term use of nonsteroidal anti-inflammatory drugs, neurofibromatosis, liver transplantation, primary and metastatic adrenal tumors, heparin-associated thrombocytopenia, anticoagulation, sepsis, and anti-phospholipid antibodies [2][3][4]. Adrenal hemorrhage could be spontaneous [2], and sometimes has clinical and radiographic features of adrenal neoplasm [2,3,[5][6][7][8][9]. So far there were no reports of adrenal hematomas in patients with idiopathic thrombocytopenic purpura (ITP).…”
Section: Introductionmentioning
confidence: 99%